2004
DOI: 10.1038/ncb1196
|View full text |Cite
|
Sign up to set email alerts
|

The Williams syndrome transcription factor interacts with PCNA to target chromatin remodelling by ISWI to replication foci

Abstract: Chromatin states have to be faithfully duplicated during DNA replication to maintain cell identity. It is unclear whether or how ATP-dependent chromatin-remodelling factors are involved in this process. Here we provide evidence that the Williams syndrome transcription factor (WSTF) is targeted to replication foci through direct interaction with the DNA clamp PCNA, an important coordinator of DNA and chromatin replication. WSTF, in turn, recruits imitation switch (ISWI)-type nucleosome-remodelling factor SNF2H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
180
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(190 citation statements)
references
References 34 publications
10
180
0
Order By: Relevance
“…28,59,60 In earlier studies WSTF, a subunit of the WICH remodeling complex, had been shown to bind to replication sites by interacting with PCNA. 17 We found that SMARCAD1 also physically interacts with PCNA both in vitro and in vivo, supporting a model in which SMARCAD1 acts at replication sites to restore heterochromatin organization chromatin modifying activities to replication. 9 SMARCAD1 predominantly associates with factors linked to transcriptional repression, replication and repair (Fig.…”
Section: Directing Remodeling To Sites Of Replicationmentioning
confidence: 62%
See 2 more Smart Citations
“…28,59,60 In earlier studies WSTF, a subunit of the WICH remodeling complex, had been shown to bind to replication sites by interacting with PCNA. 17 We found that SMARCAD1 also physically interacts with PCNA both in vitro and in vivo, supporting a model in which SMARCAD1 acts at replication sites to restore heterochromatin organization chromatin modifying activities to replication. 9 SMARCAD1 predominantly associates with factors linked to transcriptional repression, replication and repair (Fig.…”
Section: Directing Remodeling To Sites Of Replicationmentioning
confidence: 62%
“…Most PCNA interacting factors, including WSTF, bind via a conserved motif referred to as the PCNA interacting protein (PIP) box. 17,61 Several putative PIP boxes were identified in SMARCAD1, yet their mutagenesis had no apparent effect on the observed co-localization of SMARCAD1 with PCNA (data not shown). SMARCAD1 may thus belong to a group of proteins that bind PCNA via different, non-conserved sequences.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…ACF1-SNF2h was reported to be essential for the replication of heterochromatin in cultured mammalian cells (Collins et al, 2002). Other evidence showed that ISWI type nucleosome remodeling complex SNF2h is recruited to replication fork by WTSF, RNAi mediated knock down of SNF2h or WTSF caused reduction of DNA replication efficiency during S phase (Poot et al, 2004). In S. cerevisia INO80 complex is enriched in replication origins and stalled replication forks under replicative stress (Papamichos-Chronakis and Peterson, 2008;Vincent et al, 2008).…”
Section: Disassembly Of Chromatin Structure Ahead Of Replication Forkmentioning
confidence: 99%
“…PCNA directly interacts with a series of chromatin modifying enzymes, and potentially recruits them to replication foci. These factors include CAF-1 (Shibahara and Stillman 1999;Moggs et al, 2000), HDACs (Milutinovic et al, 2002), ATP dependent chromatin remodeling complex WSTF-SNF2h (Poot et al, 2004), histone lysine methyltransferse PR-SET7 (Jørgensen et al, 2007;Huen et al, 2008) and DNA methyltransferase DNMT1 (Leonhardt et al, 1992;Chuang et al, 1997). CAF-1 is also reported to interact with chromatin factors, including MBD1 (methyl CpG-binding protein 1) and SETDB1 during heterochromatin DNA replication (Reese et al, 2003;Sarraf and Stancheva, 2004).…”
Section: Inheritance Of Epigenetic Marks Behind the Replication Fork?mentioning
confidence: 99%